The Influence of Work Culture on the Effectiveness of Internal Audit: A Qualitative Study - Surya, Fransiska; Pramudita, Tan; Wijaya, Dina; Permadi, Dodi; Putri, Eka (Manunggal Halim Jaya, 2023)
This qualitative study investigates the influence of organizational culture on the effectiveness of internal audit processes within organizations. Through a comprehensive literature review and supplementary data collection methods, including interviews with internal auditors and organizational leaders, the study explores the intricate relationship between work culture and internal audit outcomes. The research draws on theoretical frameworks such as agency theory and social identity theory to conceptualize the influence of organizational culture on audit practices and performance. The findings reveal that a strong organizational culture characterized by ethical norms, transparency, and accountability enhances internal audit effectiveness by fostering trust, compliance, and collaboration among employees. Conversely, a weak or dysfunctional culture may impede audit effectiveness by hindering communication, collaboration, and compliance. The study highlights the importance of cultivating a supportive culture that aligns with audit objectives to optimize audit outcomes and promote organizational success. These insights contribute to a deeper understanding of the mechanisms through which organizational culture influences internal audit effectiveness and offer practical implications for organizations seeking to enhance audit performance and organizational resilience.